As crianças do último ano da educação infantil e sua relação com a aprendizagem da escrita: sujeitos, móbeis e sentidos - Oliveira, Rejane Maira Dias de (2018)
The purpose for the making of this dissertation was the realization of teaching techniques dedicated to the instruction of the written language based on repetitive activities and training in the Child Education’s context on the Public Net of Teaching in the City of Fortaleza - CE. Based on this constatation, the goal that was set was analyzing the relationship built by the children from the Public Net of Teaching with the learning of writing, considering these subjects in their activities, motives and meanings towards the knowing of how to write. The theoretical basis for the research was built from the concepts of agent, activity, motives and meanings, produced by Charlot (2000, 2013) to discuss the relationship with the knowledge, in the field of Sociology of Education and its proposition of a Sociology of the Subject. The research has a qualitative nature, with as locus of development a school from the public net of teaching in the city of Fortaleza and as subject individuals the children at the grade named Infantile V (or kindergarten), between five and six years old. The techniques to the construction of data consisted in participating observation and a ludic activity that was appropriate to the children’s age, that allowed us get in their experiences and relationships with the learning of the written language. The ways of register had as ressosurces the field journal, photographs and tapes of the children speaking. However, among these ressources, only the notes from the field journal and the transcriptions of the tapes were used as data to be analysed, according to the qualitative methods in the analysis of the matter that allowed us the construction of ideal types (CHARLOT, 2001) of the relationship between the children and the learning of how to write. The other ressources were used as support to the possible inferences concerning the meanings the children give to this learning. The analysis’ results of the data point to the construction of three ideal types: 1) the writing as institutional precept; 2) the writing as situational competence and 3) the writing as intelectual subject. The interpretation of dominant trends, revealed in these ideal types and that guide the children’s relationships with the learning of writing, is what allows us, therefore, to know the place the children occupy as subject individuals of this learning, their motives to learn to write and the meanings they give to this activity.